Genotypic and Phenotypic Aspects of Longevity: Results from a Sicilian Survey and Implication for the Prevention and Treatment of Age-related Diseases - Accardi, Giulia; Aprile, Stefano; Candore, Giuseppina; Caruso, Calogero; Cusimano, Rosanna; Cristaldi, Laura; Di Bona, Danilo; Duro, Giovanni; Galimberti, Damiano; Gambino, Caterina M.; Ligotti, Mattia Emanuela; Mazzucco, Walter; et al. (Current Pharmaceutical Design, 2019)
Background: It is well known that long living individuals are a model of successful ageing and that the identification of both genetic variants and environmental factors that predispose to a long and healthy life is of tremendous interest for translational medicine. Methods: We present the preliminary findings obtained from an ongoing study on longevity conducted on a sample of Sicilian long-lived individuals. Results: We review the characteristics of longevity in Sicily, taking into account lifestyle, environment, genetics, hematochemical values, body composition and immunophenotype. In addition, we discuss the possible implications of our data for the prevention and/or treatment of age-related diseases. Conclusion: As widely discussed in this review, the explanation of the role of genetics and lifestyle in longevity can provide important information on how to develop drugs and/or behaviours that can slow down or delay ageing. Thus, it will be possible to understand, through a “positive biology” approach, how to prevent and/or reduce elderly frailty and disability.
Keywords: body composition